ZrO2/Cr Multilayer Coating for the Protection of E110 Zirconium Alloy from High Temperatures; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17, iss. 5 - Sidelev D. V. Dmitry Vladimirovich; Ruchkin S. E. Sergey Evgenjevich; Syrtanov M. S. Maksim Sergeevich; Pirozhkov A. V. Alexey Vladimirovich; Maksimov P. N. Prokopy Nikolaevich (2023, 2023)
Title screen